India’s position on the key legal documents relating to the Non-Proliferation of nuclear weapons as a challenge to the international nuclear security - Дорош, Леся; Безнісько, Анна; Dorosh, Lesia; Beznisko, Anna (Lviv Politechnic Publishing House, 2017)
Досліджено позицію Індії щодо основних міжнародних договорів та ініціатив у сфері нерозповсюдження ядерної зброї, а також вплив політики країни у ядерній сфері на функціонування режиму нерозповсюдження ядерної зброї. Проаналізовано причини, чому країна воліє утриматися від підписання основних документів у сфері нерозповсюдження ядерної зброї. Стверджено, що неприєднання Індії до вказаних ініціатив є дестабілізуючим фактором, який підриває систему режиму нерозповсюдження ядерної зброї в світі.

It is investigated India’s position on major international treaties and initiatives in the field of nuclear weapons nonproliferation (Treaty on the Non-Proliferation of Nuclear Weapons (NPT), Comprehensive Nuclear-Test-Ban Treaty (CTBT), Fissile Material Cutoff Treaty (FMCT)). In addition, it is analysed the impact of the country’s policy in the nuclear field on the functioning of the nuclear non-proliferation regime. It is found that according to the National Indian nuclear doctrine, one of the important tasks of national security is general non-discriminatory nuclear disarmament aimed at the quickly achievement of a nuclear-free world. It is analyzed the reasons of the country’s refusal to sign the basic documents in the sphere of non-proliferation of nuclear weapons. Firstly, the NPT (1968) is discriminatory, since it gives more rights and authorities to the nuclear states and thereby limits the rights of the non-nuclear states. In addition, it is not capable to provide security of the non-nuclear states in case of attack by the nuclear states. Secondly, the CTBT (1996) does not contain specific terms of eliminating of nuclear weapons, and also allows the so-called sub-critical nuclear tests. At last, the FMCT will not be signed, because India is threatened by China – a member of the “nuclear club”, and neighbouring Pakistan, thereby the only way to ensure the security of the people and strengthen its position in the region is to increase the India’s nuclear potential. It is alleged that India’s non-alignment to these initiatives is a destabilizing factor that undermines the whole system of non-proliferation regime in the world. It is proved the necessity (within the framework of the legal acts that make up the basis of the non-proliferation regime) to develop and offer a set of interconnected measures for stabilizing the situation in the region, mainly between India and Pakistan, and to provide a prospect for its improvement and ensure the international nuclear security.
Позиція Індії щодо ключових нормативно-правових документів у сфері нерозповсюдження ядерної зброї як виклик міжнародній ядерній безпеці
Keywords: ядерна безпека; Індія; ядерна зброя; ядерне роззброєння; Договір про нерозповсюдження ядерної зброї; nuclear security; India; nuclear weapons; nuclear disarmament; the Treaty on the Non-Proliferation of Nuclear Weapons; 327.374; 341.675(540)